New sightings of the Southern right whales in West Antarctic Peninsula waters - O. Savenko; A. Friedlaender (Український антарктичний журнал, 2022)
Southern right whales (SRW) in the southwest Atlantic are recognized as slowly recovering after the massive population decline induced by harvesting. SRWs spend summer months in high-latitude feeding grounds and migrate to mid-latitude wintering grounds in autumn, where breeding occurs. Only a few sightings are known for the Antarctic waters as far south as 64° S. The West Antarctic Peninsula is a biologically productive area experiencing marine ecosystem transformations caused by climate changing at one of the fastest rates on Earth. The continental shelf of this region is important for krill stocks — a key prey source for SRW. The purpose of the present study was to reveal the austral summer and autumn presence of the SRWs in the waters of the West Antarctic Peninsula. In May—June 2009, vessel observations were made during a National Science Foundation research cruise. In March 2014, opportunistic surveys were conducted by researchers using the tour vessel as a platform of opportunity. During late March and April of 2018, January — July 2019 and March — April 2020, regular boat-based observations and vessel surveys were conducted in frames of the XXIII and XXIV Ukrainian Antarctic Expeditions, based at the Ukrainian Antarctic Akademik Vernadsky station. In our study we discuss four sightings of SRWs occurred at south of 64° S (2), and 65° S (2). On May 7, 2009, a single adult foraging SRW was sighted in Wilhelmina Bay. On March 22, 2014, an adult SRW was resting with two adult humpback whales in the northern part of the Lemaire Channel. On April 7, 2018, one SRW was sighted in a group with four humpback whales, and intensive interspecies social interactions happened. The last encounter of the SRW happened on April 24, 2020, in Gerlache Strait, near the southeastern coast of the Brabant Island — a single adult right whale was noticed while travelling. Results of our study indicate the autumn presence of some SRWs in the West Antarctic Peninsula waters — on the edge of the southern limit of known distribution for the species.